Diagnostic Utility of Integrated11C-Pittsburgh Compound B Positron Emission Tomography/Magnetic Resonance for Cerebral Amyloid Angiopathy: A Pilot Study - Chang, Yan; Liu, Jiajin; Wang, Liang; Li, Xin; Wang, Zhenjun; Lin, Mu; Jin, Wei; Zhu, Mingwei; Xu, Baixuan (Frontiers in Aging Neuroscience, 2021)
Objective: We aimed to compare amyloid deposition at the lobar cerebral microbleed (CMB) sites of cerebral amyloid angiopathy (CAA), Alzheimer’s disease (AD), and cognitively normal healthy controls (NC) and to propose a novel diagnostic method for differentiating CAA patients from AD patients with integrated 11C-Pittsburgh compound B (PIB) positron emission tomography (PET)/magnetic resonance (MR) and assess its diagnostic value. Methods: Nine CAA, 15 AD patients, and 15 NC subjects were enrolled in this study. Each subject underwent an 11C-PIB brain PET/MR examination. Susceptibility weighted imaging was assessed to detect CMB locations, and standardized uptake value ratios (SUVRs) were measured at these sites. Cortical PIB distributions were quantitatively evaluated. Patients with CAA, AD, and NC subjects were compared with global and regional cortical SUVRs at CMB cites. The diagnostic accuracy of MRI, PIB-PET, and PET/MR in differentiating CAA and AD was evaluated. Results: Lobar CMBs were detected in all the CAA patients, eight of the 15 AD patients (53.3%), and four of the 15 NC subjects (26.7%), respectively. The PIB deposition at CMB sites was significantly higher in CAA patients compared with AD patients and NC subjects in terms of SUVR (1.72 ± 0.10 vs. 1.42 ± 0.16 and 1.17 ± 0.08; p < 0.0001). The PIB deposition was associated with CMB locations and was greatest in the occipital and temporal regions of CAA patients. The global cortical PIB deposition was significantly higher in CAA than in NC subjects (1.66 ± 0.06 vs. 1.21 ± 0.06; p < 0.0001) and significantly lower than in AD patients (1.66 ± 0.06 vs. 1.86 ± 0.17; p < 0.0001). In contrast, the occipital/global PIB uptake ratio was significantly increased in CAA (occipital/global ratio, 1.05 ± 0.02) relative to AD patients (1.05 ± 0.02 vs. 0.99 ± 0.04; p < 0.001). PET/MR had a higher accuracy (sensitivity, 88.9%; specificity, 93.3%) than separate PET and MR. Conclusion: Our results indicate that the CMBs occur preferentially at loci with concentrated amyloid. By combining lobar CMBs with regional cortical amyloid deposition, the proposed workflow can further improve CAA diagnostic accuracy compared to each method alone. These findings improve our knowledge regarding the pathogenesis of CMBs and highlight the potential utility of PIB-PET/MR as a non-invasive tool for distinguishing CAA and AD patients.